The church cap and the crypt cap: Early modern knitted fragments found in Denmark - Ringgaard, Maj (Archaeological Textiles Review, 2018)
Two Early Modern knitted caps are compared in terms of the quality of the fabric and way they were constructed. One is a flat cap which was probably knitted in the round on more than two needles. It was found in 2014 amongst rubbish on the site of a naval shipyard under a building dating to 1562. This suggests it is the oldest knitted fabric in Denmark known to date. The other cap is a brimless, head-hugging style which lay unnoticed in the National Museum of Denmark’s collection for almost a century. The dating is uncertain but it is likely to be 17th century. This was probably not knitted in the round but worked back and forth with two needles or on a knitting frame.